Organization of the cysts in bee (Hymenoptera, Apidae) testis: number of spermatozoa per cyst - Cruz-Landim, Carminda da [UNESP] (Fundação Zoobotânica do Rio Grande do Sul, 2001)
The morphology of the cyst cells in Apis mellifera Linné, 1758, Scaptotrigona postica Latreille, 1804, and Melipona bicolor bicolor Lepeletier, 1836 testis, as well as the average number of spermatic cells are reported. The data indicates a supporting and nourrishing role of the cyst cells to the developing cystocytes. The counts of immature spermatozoa in the cysts show an average of 202.8 ± 21.2 spermatozoa for A. mellifera, 117.4 ± 8.68 for S. postica and 88.8 ± 15.57 for M. bicolor, which predict the occurrence of 8 mitotic cycles in the cystocytes of A. mellifera and 7 in the meliponines, considering that only one spermatozoom originates of each final spermatogonium.
Keywords: Cyst cell; cell number average; testis; bees